2022
DOI: 10.1002/mp.15718
|View full text |Cite
|
Sign up to set email alerts
|

Ultralow‐parameter denoising: Trainable bilateral filter layers in computed tomography

Abstract: Background Computed tomography (CT) is widely used as an imaging tool to visualize three‐dimensional structures with expressive bone‐soft tissue contrast. However, CT resolution can be severely degraded through low‐dose acquisitions, highlighting the importance of effective denoising algorithms. Purpose Most data‐driven denoising techniques are based on deep neural networks, and therefore, contain hundreds of thousands of trainable parameters, making them incomprehensible and prone to prediction failures. Deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Hence, in our case, the minimization of the TV norm needs to be achieved by cupping correction rather than noise reduction. It has already been demonstrated that incorporating a denoiser based on supervised learning into the proposed pipeline yields state‐of‐the‐art results 49 . Investigating a joint denoising and cupping correction approach can be an interesting avenue for future work.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Hence, in our case, the minimization of the TV norm needs to be achieved by cupping correction rather than noise reduction. It has already been demonstrated that incorporating a denoiser based on supervised learning into the proposed pipeline yields state‐of‐the‐art results 49 . Investigating a joint denoising and cupping correction approach can be an interesting avenue for future work.…”
Section: Discussionmentioning
confidence: 97%
“…It has already been demonstrated that incorporating a denoiser based on supervised learning into the proposed pipeline yields state-of-the-art results. 49 Investigating a joint denoising and cupping correction approach can be an interesting avenue for future work.…”
Section: Discussionmentioning
confidence: 99%
“…In this work, some exemplary results of other algorithms are also displayed as a comparison. The bilateral filter 47 and its trainable version 48 are applied to compare with well-known adaptive www.nature.com/scientificreports/ filters. In particular trainable bilateral filter versions have been shown to provide robust denoising performance in the context of medical imaging 49 .…”
Section: Methodsmentioning
confidence: 99%
“…Noise2Self and Noise2Void are well-known self-supervised denoising algorithms. In our experiments, three trainable bilateral filter layers are trained in a self-supervised way using the Noise2Void method following the setup of Wagner et al 48 .…”
Section: Methodsmentioning
confidence: 99%
“…In our previous work, we presented a trainable bilateral filter with competitive denoising performance that can be included in a differentiable pipeline and optimized in a data-driven fashion 29 . However, the prediction of bilateral filter layers is solely dependent on three learned spatial parameters and one intensity parameter 9 .…”
mentioning
confidence: 99%